(NgIDROBIOLOGI^ESKIJ REVIM MALYH REK W USLOWIQH ANTROPOGENNOGO WOZDEJSTWIQ (B/s - (NbALODE(B, (NmAJQ qNOWNAs; (NgAJLE(B, (NmARA qNOWNAs; (NzANDMANE(B, (NaSTRIDA kARLOWNAs; (NzWAJGZNE(B, (NmAJQ vANOWNAs; (NaNDRU[AJTIS(B, (Ng(B.(Np(B.s; (NkA^ALOWA(B, (No(B.(Nl(B.s; (NiNSTITUT BIOLOGII an lATWssrs ((NrIGA (B:s (NzINATNE(B,s, 1981)
(NrEZ(B. (NANGL(B.s
(NsPISOK LIT(B.: (NS(B. 147-152; (NuKAZ(B.: (NS(B. 153-160s
Keywords: (NgIDROBIOLOGIQs; (NaNTROPOGENNOE WOZDEJSTWIEs